An assessment of case-fatality and infection-fatality rates of first and second COVID-19 waves in Italy: COVID-19 fatality rate in Italy - Filippini, Tommaso; Zagnoli, Federico; Bosi, Matteo; Giannone, Maria Edvige; Marchesi, Cristina; Vinceti, Marco (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The exact COVID-19 severity is still not well defined and it is hotly debated due to the a few methodological issues such as the uncertainties about the spread of the SARS-CoV-2 infection. Methods: We investigated COVID-19 case-fatality rate and infection-fatality rate in 2020 in Italy, a country severely affected by the pandemic, basing our assessment on publicly available data, and calculating such measures during the first and second waves. Results: We found that province-specific crude case-fatality rate in the first wave (February-July 2020) had a median value of 12.0%. Data about infection-fatality rate was more difficult to compute, due to large underestimation of SARS-CoV-2 infection during the first wave when asymptomatic individuals were very rarely tested. However, when using as a reference population-based seroprevalence data for anti-SARS-CoV-2 antibodies collected in May-July 2020, we computed an infection-fatality rate of 2.2%. During the second wave (Sep-Dec 2020), when SARS-CoV-2 testing was greatly increased and extended to many asymptomatic individuals, we could only compute a ‘hybrid’ case/infection-fatality rate with a value of 2.2%, similar to the infection-fatality rate of the first wave. Conclusions: Overall, this study allowed to assess the COVID-19 case- and infection-fatality rates in Italy before of variant spread and vaccine availability, confirming their high values compared with other airborne infections like influenza. Our findings for Italy were similar to those characterizing other Western European countries.